Progresses at CEA on EU demo reactor cryomagnetic system design activities and associated R&D. (4th July 2019) - Zani, L.; Bonne, F.; Ciazynski, D.; Decool, P.; Gros, G.; Hoa, C.; Hertout, P.; Lacroix, B.; Lamaison, V.; Le Coz, Q.; Misiara, N.; Nicollet, S.; et al.
Abstract: The EU DEMO reactor is expected to be among the first applications of fusion for electricity generation in the near future and the design of its magnet system is of central importance as driving power plant performance, budget and production efficiency. In this purpose activities were led by CEA in the framework of EUROfusion Consortium to contribute to the EU DEMO magnet system design. It encompassed design activities (dimensioning and development of associated modelling tools) with R&D (design and tests of mock-ups). The CEA design activity was mainly oriented towards Toroidal Field (TF) coils system to propose a conceptual option (pancake-wound, no radial plates) established with a semi-analytical CEA tool that considers the inter-dependent electromagnetic and mechanical behaviors. Then the proposed design is consolidated by detailed analyses: Thermo-hydraulics evaluation by coupling THEA, TRAPS and CAST3M softwares respectively for thermo-hydraulics, electromagnetic and thermal items. The outcomes obtained in normal and off-normal regimes are exposed and discussed in the paper; Mechanics evaluation with the most stressed zones identified and their criticity evaluated, in particular in the insulation zones. Design optimization analyses were conducted on jacket shape, together with investigations on the thermo-mechanic hotspot criterion. Further to the TF system, the central solenoid design was addressed and an optimization analysis will be presented and discussed. On another side, CEA also conducted R&D activities, mostly regarding the TF system with hydraulic tests at variable void fraction to explore its impact on helium friction and a full-scale TF conductor sample design and manufacture.